Atributos genéticos, morfofisiológicos e agronômicos de subamostras de arroz e feijão do Pantanal Mato-Grossense - Oliveira, Glauce Portela de (2016)
Farmers within the district of São Pedro de Joselândia, in the municipality of Barão de Melgaço, state of Mato Grosso, cultivate two rice and three bean varieties that do not have commercial origins. Considering that the genetic material of agricultural produce are relatively limited, any unknown variety is a potential source of genetic variability. Therefore, the objective of this work is to determine the characteristics of these sub-samples of rice and beans. All sample materials were germinated in pots in green-house conditions similar to those of the Pantanal wetland and fertilized with NPK. The photosynthetic efficiency, water use efficiency and yield were evaluated for all samples. We determined that the subsamples of rice and beans are in fact traditional varieties, different from those catalogued by EMBRAPA (the Brazilian Agency of Agriculture and Livestock) in the Core Collection of Rice and Beans. This benefits the community both via their ownership of this unique material and its adaptation to the local environment. All plant materials are morphologically distinct, both as plants and as seeds. The addition of fertilizer did not influence agronomic or morpho-physiologic characteristics, possibly due to the high natural fertility of the local soils. The varieties of rice and beans tested have potential for genetic improvement, as they are distinct from varieties previously catalogued in the core collection and may present desirable properties in terms of biotic and abiotic tolerance.